Transcription factor MEF2D regulates aberrant expression of ACSL3 and enhances sorafenib resistance by inhibiting ferroptosis in HCC - Li, Xue; Chen, Shimin; Shi, Yuanyuan; Wang, Yuanjing; Wang, Xuanzhe; Lin, Qian; Wu, Chao; Fang, Wenshuo; Sun, Peng; Ma, Leina (Frontiers in Pharmacology, 2024)
Background Sorafenib is a first-line treatment for hepatocellular carcinoma (HCC); however, acquired resistance often results in a poor prognosis, indicating a need for more effective therapies. Sorafenib induces cell death through an iron-dependent mechanism known as ferroptosis, which is closely associated with the onset and progression of HCC. Methods This study investigated the role of ACSL3 in sorafenib resistance and ferroptosis in HCC. The expression of ACSL3 was analyzed in HCC tissues and cell lines. Ferroptosis levels and cell viability were assessed in ACSL3-silenced HCC cells treated with sorafenib. The regulatory relationship between the transcription factor MEF2D and ACSL3 was evaluated using promoter binding assays and gene expression analysis. Results ACSL3 was aberrantly expressed in HCC and promoted the progression of non-alcoholic fatty liver disease (NAFLD) to HCC. Elevated ACSL3 expression inhibited ferroptosis and enhanced resistance to sorafenib. The transcription factor MEF2D directly regulated the upregulation of ACSL3 expression. MEF2D bound to the promoter regions of ACSL3 to enhance its transcription and negatively regulate ferroptosis in HCC. Conclusion This study demonstrated for the first time that MEF2D regulated ACSL3 expression and mediated sorafenib resistance by inhibiting ferroptosis in HCC, providing a potential therapeutic target for improving HCC outcomes.